2024
DOI: 10.1021/acsaelm.3c01447
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bifunctionality of YSZ Thin Films in MOS Structures: Bridging the Gap between RRAM and Super-Pseudocapacitor Technologies

Arturo Romo,
Gerardo Soto,
Hugo Tiznado

Abstract: This investigation explores the resistive switching and energy storage capabilities of 100 nm yttria-stabilized zirconia (YSZ) thin films in a metal-oxide-semiconductor (MOS) configuration. Under soft voltage and temperature conditions, the device primarily functions as a conventional MOS capacitor with excellent insulating properties. However, upon exceeding a voltage threshold of 10.5 V, the resistive switching mechanisms are triggered. The multilevel memory properties of the device were investigated by empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Similarly, Wang et al demonstrated the stable supercapacitor performance of Ni x S y /MoS 2 hybrid nanomaterials with enhanced energy storage capability . Recently, materials such as carbon compounds, transition-metal dichalcogenides, ferromagnetic shape memory alloys, perovskite materials, metal oxides, nitrides, carbides, two-dimensional (2D) conjugated metal–organic frameworks (c-MOFs), etc. have been widely used in various electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al demonstrated the stable supercapacitor performance of Ni x S y /MoS 2 hybrid nanomaterials with enhanced energy storage capability . Recently, materials such as carbon compounds, transition-metal dichalcogenides, ferromagnetic shape memory alloys, perovskite materials, metal oxides, nitrides, carbides, two-dimensional (2D) conjugated metal–organic frameworks (c-MOFs), etc. have been widely used in various electronic devices.…”
Section: Introductionmentioning
confidence: 99%